2010
DOI: 10.5713/ajas.2010.10036
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Normal Maize with Quality Protein Maize on Performance, Immune Response and Carcass Characteristics of Broiler Chickens

Abstract: An experiment was conducted to evaluate the effect of dietary replacement of normal maize (NM) with quality protein maize (QPM) on performance, immune response and carcass characteristics of broiler (Krishibro) chickens. Six experimental diets were prepared separately for starter and finisher phases. Diet 1 was a control diet formulated with NM and soybean meal. In diets 2-5, the NM was replaced with QPM at 25, 50, 75 and 100%, respectively. Diet 6 was the same as the control diet, but supplemented with synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 20 publications
2
25
1
Order By: Relevance
“…The nutritional superiority of QPM over non-QPM in poultry nutrition has been well established (Omage et al, 2009;Panda et al, 2010;Nuss and Tanumihardjo, 2011;Panda et al, 2014). In the studies referenced above, QPM was found to contain between 30 to 55% more lysine and tryptophan compared to non-QPM.…”
Section: Nutritional Value Of Quality Protein Maizementioning
confidence: 98%
See 3 more Smart Citations
“…The nutritional superiority of QPM over non-QPM in poultry nutrition has been well established (Omage et al, 2009;Panda et al, 2010;Nuss and Tanumihardjo, 2011;Panda et al, 2014). In the studies referenced above, QPM was found to contain between 30 to 55% more lysine and tryptophan compared to non-QPM.…”
Section: Nutritional Value Of Quality Protein Maizementioning
confidence: 98%
“…Protein requirement in poultry is a function of the amino acid profile, not just the crude protein content, as birds cannot synthesize essential amino acids. In maize based diets, lysine is the major limiting amino acid (Panda et al, 2010). Under commercial production systems, deficiency of this amino acid is offset by the addition of synthetic amino acids or the addition of conventional protein sources such as soybean or fishmeal.…”
Section: Nutritional Value Of Quality Protein Maizementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, to alleviate these problems, the Government of Ethiopia has set a target to have QPM varieties cultivated on 20% of the country's total maize area in the coming few years including GTP II [27]. In terms of the quantity of energy and protein it contains, QPM has no difference with the normal maize as indicated in Table 1 and Table 2 but the difference lies in protein quality because it contains double the amount of Lysine and Tryptophan compared to normal maize [1,2,28,29] and is essentially interchangeable with normal maize in cultivation and kernel phenotype [17]. The results in Table 1 indicated that the crude protein content of QPM has no significant difference from normal maize.…”
Section: Nutritional Composition Of Qpmmentioning
confidence: 99%